Case of Paraesthesia Developed After Consuming Pufferfish - Mehmet Murat Çelik; Levent Özdemir; Nazlı Deniz Ateş; Resul Akyol; Hakan Karabay; Adem Çiftci; Ömer Faruk Çelik (Galenos Yayinevi, 2021)
Pufferfish, also known globally as ballfish, globefish and toadfish, is a fish species belonging to the Tetrodontiformes family. Following the consumption of this fish, tetrodotoxin (TTX), a type of neurotoxin, causes a rare type of intoxication. This has mostly been observed in the Southeast Asian coasts, Taiwan and Japan; however, it has also been observed in the Mediterranean coastal countries in recent years. Not all species of porcupine fish are toxic; some contain only mild venom. Approximately 28 TTX analogues have been recorded to date, and some have been identified in marine organisms. In addition, TTX toxicity varies according to sex, seasons and geographic regions. In humans, TTX blocks sodium channels in the cell membrane, inducing numbness in the tongue and lips, dizziness, vomiting, tingling and numbness in the extremities, tachycardia, hypotension and paralysis. This case report aimed to provide information about the risks, toxicity and treatment methods in people exposed to TTX.